2017
DOI: 10.1080/13102818.2017.1379360
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic control in type 1 diabetes mellitus among Bulgarian children and adolescents: the results from the first and the second national examination of HbA1c

Abstract: View related articles View Crossmark data Citing articles: 4 View citing articles ARTICLE; MEDICAL BIOTECHNOLOGY Glycemic control in type 1 diabetes mellitus among Bulgarian children and adolescents: the results from the first and the second national examination of HbA 1c

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…As a result, if increasing the age of children by one year, the patient is more likely to develop poor glycemic control. This finding was supported by studies conducted in Amhara region, Egypt, and Bulgaria, which showed that patients with poor control had a significantly higher mean age 2 , 17 , 37 . The possible reason is due to the fact that this study includes pediatric patients which also include adolescents and they are more prone to poor diabetic control because of pubertal stress or may not be safely follow their treatment.…”
Section: Discussionsupporting
confidence: 56%
“…As a result, if increasing the age of children by one year, the patient is more likely to develop poor glycemic control. This finding was supported by studies conducted in Amhara region, Egypt, and Bulgaria, which showed that patients with poor control had a significantly higher mean age 2 , 17 , 37 . The possible reason is due to the fact that this study includes pediatric patients which also include adolescents and they are more prone to poor diabetic control because of pubertal stress or may not be safely follow their treatment.…”
Section: Discussionsupporting
confidence: 56%
“…After the first evaluation in 2012, in which the HbA 1c median level of 8.93% § 1.98% was found rather unsatisfying, additional training for the patients and their parents was conducted the following years. In 2014, we performed a second study and found a significantly lower level of HbA 1c (8.42% § 1.69%) compared to that in 2012 (p < 0.001) [13]. Below, we analyse and discuss the impact of some of the examined social factors on the glycaemic control in children and adolescents with type 1 of diabetes mellitus.…”
Section: Descriptive Statisticsmentioning
confidence: 94%
“…[ 3 ] Healthy women are known to have lower insulin sensitivity than healthy men, but this is physiologically compensated for by higher insulin secretion. [ 5 13 ] Hormonal changes may also have a role as girls reach puberty earlier than boys. [ 3 ]…”
Section: Discussionmentioning
confidence: 99%